Driving Factors of Consumer to Purchase Furniture Online on IKEA Indonesia Website - Trisha Gilang Saraswati (Jurnal Sekretaris dan Administrasi Bisnis, 2018)
The tendency of consumers in shopping for furniture is very different from shopping for other goods or services, because furniture is expected to be stored and used in a long time. Considering that, consumers tend to want to shop directly to offline stores in order to see, feel and check quality directly because of many aspects that are assessed such as the quality of materials, models, colors and more. Behind the trend to shop furniture offline, IKEA continues to innovate to improve the performance of its website so that consumers can shop online. Therefore, this study intends to analyze what factors are driving consumers in shopping for furniture online especially on the website of IKEA Indonesia. From two grounded theory employed on this research, there are 14 factors that can influence consumers to buy online. This data analysis uses Principal Component Analysis (PCA), a factor analysis method that extracts factors by using total variance in the analysis. From data calculation, it is known that there are 8 driving factors of consumer to purchase furniture online on IKEA Indonesia’s website: Enjoyment, Perceived Risk, Efficiency, Service & Merchandise Quality, Ease of Navigation, Price Attractiveness, Flexibility and Reliability. By knowing what factors can affect consumers in doing online shopping for furniture, companies in this case IKEA Indonesia can optimize the use of its website in accordance with influential factors. Keywords: Retail Business, Online Purchase Decision, Factor Analysis